Simulation Study of Sensitivity Performance of MEMS Capacitive Bending Strain Sensor for Spinal Fusion Monitoring. (17th December 2012) - Abdul Mokti, Muhammad Irsyad; Abd Rahim, Inzarulfaisham
Abstract : This study evaluates the sensitivity of microelectromechanical system (MEMS) capacitive bending strain sensor with a double layer cantilever designed to meet the requirements of spinal fusion monitoring. The cantilever structure of the sensor consists of two parallel substrate plates which constitute the electrodes, attached to an anchor made of silicon dioxide. The sensor was able to monitor bending strain value ranging from 0 to 1000 με . In order to evaluate the sensitivity of the sensor, parametric study was carried out by varying electrode gap, anchor length, and dielectric coverage between the electrodes. The nominal capacitive strain sensor for various applications has sensitivity ranging from 255 aF/ με to 0.0225 pF/ με . An increase in the sensitivity was observed on reducing the electrode gap and the anchor length and increasing the dielectric coverage, resulting in a highest sensitivity value of 0.2513 pF/ με . It was also observed that dielectric constant has a significant effect on the sensitivity behavior of the sensor.